Zastosowanie analizy konwersacyjnej w dydaktyce akademickiej - Nowicka, Agnieszka (Neofilolog, 2021)
The article discusses a case study focusing on the students’ task of analyzing expressing opinions in Polish and English TV discussions. The written observation task is performed as a final requirement to receive credit for the course of interaction analysis, during which the second-year students of applied linguistics are introduced to the basic methods of conversation analysis. I use document analysis of students’ discourse to distinguish the main tendencies in performing the task by the students. The aim of the research presented in the paper is assessing the students’ ability to use conversation analysis in observing different ways of expressing opinion in selected Polish and American TV discussions. I especially focus on evaluating the students’ skill of unmotivated looking at the ways of expressing opinions in TV discussions. This phenomenological observation requires suspending the researcher’s personal views and assumptions concerning the meaning of actions in interaction. The main aim of conversation analysis is discovering the meaning of communicative actions from the perspective of a talk participant. If applied appropriately, this kind of observation allows student-researchers to avoid a tendency to rely on stereotypical evaluations in the analysis of interactions.